The - Gould, John A. (Lynne Rienner Publishers, 2011)
In this remarkable story of postcommunist politics gone wrong, John Gould explores privatization s role in the scramble for wealth and power in postcommunist Europe. Gould engages the core debates on privatization. Does democratic development facilitate effective capitalist reform, or vice versa? How do political legacies shape privatization choices? Is simultaneous transition feasible? Offering both new empirical information and nuanced political analysis, his in-depth study reveals a surprising relationship between political liberalization and economic reform